Perkembangan Entrepreneur di Malang: Studi Proses, Fase Perkembangan, dan Model yang Berkelanjutan - Armanu, Armanu; Novadjaja, Lily Hendrasti; Noermijati, Noermijati (Universitas Brawijaya, Indonesia, 2011)
The study aims to describe (1) the creation process of entrepreneur, (2) the entrepreneur development face, and (3) the sustainable entrepreneur model. Qualitative approach with fenomenological method were utilized to get the description. The study found that (1) the entrepreneur was created through family life and work experiences; (2) the entrepreneur development process through product innovation, process innovation and marketing innovation, and (3) strengtherning